Structural Exploration of Phantom Oligoguanidine from Asymmetric Diamine and Guanidine Hydrochloride. Issue 16 (9th June 2016) - Wang, Hui; Bethke, Christian; Hermann, Markus; Frenking, Gernot; Agarwal, Seema
Abstract : Condensation reaction of asymmetric triamine (spermidine) with guanidine hydrochloride provides a phantom structure with selective formation of rings in the repeat unit. The intermolecular condensation between amine and guanidine hydrochloride can provide either a linear structure or six‐ or seven‐membered rings in the repeat unit by elimination of one or three molecules of ammonia, respectively, per repeat unit. The preference of formation of rings and mechanistic aspects are studied by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry, 1D, 2D NMR, and quantum chemical calculations. Abstract : Condensation product of asymmetric triamine and guanidine hydrochloride shows a nonlinear repeat unit (phantom) structure as seen by matrix assisted laser deionization time‐of‐flight mass spectrometry and 1D and 2D NMRs. The analytical methods have limitation in determining the exact ring‐size, which is made possible by quantum chemical calculations.